The Relationship between Oral Health-Related Factors and Grip Strength in the Elderly - Ki-Eun Kim (The Korean Society of Dental Hygiene Science, 2022)
Background: Among the health problems in old age, oral health is closely related to nutrition intake and digestion, so although it is an important factor in the well-being of the elderly along with general health, studies examining the relationship between oral health-related factors and grip strength of the elderly are insufficient. Therefore, this study intends to examine the relationship between oral health-related factors and grip strength, which are closely related to the general health of the elderly.Methods: This study used data from the 7th period of Korea National Health and Nutrition Survey (2016∼2018) approved by the Research Ethics Review Committee of the Korea Centers for Disease Control and Prevention. Complex sample frequency analysis and descriptive statistics were performed, and general linear model analysis was performed to confirm the relationship between demographic characteristics, oral health -related factors and grip strength. The statistical analysis was performed using IBM SPSS Statistics for Windows, Version 23.0, and the significance test was based on type I error level of 0.05.Results: Grip strength was higher in the case of no discomfort than in the case of discomfort in relation to mastication discomfort and grip strength (B=0.927, p＜0.001). In addition, the grip strength was decreased by 1.348 times when not using dental floss (p＜0.001) and when not using mouth wash was 1.480 times (p＜0.001).Conclusion: In this study, in the relationship between oral health-related factors and grip strength, grip strength was found to be high in the absence of mastication discomfort. and in the case of using dental floss and mouthwash the elderly showed high grip strength. Therefore, it is suggested to present a lifestyle to improve hand function and grip strength in the elderly and develop a program to increase grip strength and provide them at the same time during oral health education.